Rattus xanthurus Gray 1867 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus xanthurus Gray 1867 Rattus xanthurus Gray 1867, Proc. Zool. Soc. Lond., 1867: 598. Type Locality: Indonesia, NE Sulawesi, Tondano, 3600 ft (1100 m). Vernacular Names: Northeastern Xanthurus Rat. Synonyms: Rattus faberi (Jentink 1883); Rattus paraxanthus (Sody 1941). Distribution: NE Sulawesi only, from vicinity of Teluk Kuandang (0°50'N, 122°52'E) eastward in NE region of N peninsula of Sulawesi. Conservation: IUCN – Lower Risk (lc). Discussion: Rattus xanthurus species group. See Musser (1971 c-e , 1984) for justification behind allocation of synonyms. One of the larger-bodied members of this complex, which includes R. bontanus , R. marmosurus , R. salocco , and R. pelurus . Occurs sympatrically with R. marmosurus on the NE Peninsula. Sody (1941) included xanthurus in Taeromys . Although the R. xanthurus group may eventually be removed from Rattus (Musser and Holden, 1991), it does not belong in Taeromys (Musser, ms). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Muridae, pp. 1189-1531 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 1494, DOI: 10.5281/zenodo.7316535